(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study explores the transformative effects of fintech on established banking practices and structures. Financial technology (fintech) has profoundly impacted traditional banking models, ushering in a new era of financial services characterized by innovation, efficiency, and accessibility. Fintech has intensified competition within the financial sector by introducing novel technologies and business models that challenge conventional banks. Innovations such as digital wallets, blockchain, and peer-to-peer lending platforms have disrupted traditional banking services, offering consumers more convenient, cost-effective, and personalized options. This competitive pressure has compelled traditional banks to adopt new technologies and enhance their service offerings to maintain relevance. Customer experience has been revolutionized by fintech’s emphasis on convenience and personalization. Mobile banking apps and digital platforms provide 24/7 access to financial services, while advanced data analytics and artificial intelligence enable highly tailored financial products and services. These improvements in customer service have raised expectations and driven banks to innovate in response. Fintech’s cost efficiency and operational agility contrast sharply with traditional banks’ more rigid structures. Digital-only operations and automation have reduced overheads and streamlined processes, challenging banks to rethink their cost structures and service delivery methods. Additionally, fintech has advanced financial inclusion by reaching underserved populations and utilizing alternative credit scoring models. The regulatory landscape has become increasingly complex as fintech innovations intersect with traditional banking practices. Balancing innovation with regulatory compliance remains a significant challenge for both fintech firms and established banks. Overall, fintech has reshaped the financial services industry by enhancing competition, improving customer experiences, and driving operational efficiencies, prompting traditional banks to adapt and innovate in a rapidly evolving market.